Serials Spoken Here–Reports of Conferences, Institutes and Seminars. Issue 1 (2nd January 2017) - Blythe, Kurt; Aghazarian, Maria; Bhatt, Anjana H.; Becker, Rachel; Coleman, Gordon; DePope, Leigh Ann; DeRosa, Kimberly; Ford, Dianne; Galey, Molly; Kimbrough, John; Kohl, Laura; Naranch, Camelia; et al.
ABSTRACT: This quarter's column offers a report from the Acquisitions Institute at Timberline Lodge, held May 14–17, 2016, in Timberline Lodge, Oregon, and also provides coverage of multiple sessions from the Kraemer Copyright Conference, held June 6–7, 2016, in Colorado Springs, Colorado. Some reports are collected, as well, from the NASIG Annual Conference, held June 9–12, 2016, in Albuquerque, New Mexico, and the American Library Association (ALA) Annual Conference, held June 23–28, 2016, in Orlando, Florida. Lastly, there is a report from the International Federation of Library Associations and Institutions (IFLA) World Library and Information Congress, held August 13–19, 2016, in Columbus, Ohio. Topics covered include open access, linked data, copyright, text mining, e-resource management, and digitization.